Bioregions and Spirit Places: Taking up Jim Dodge’s Long-Lost Suggestion - McCann, Greg (The Trumpeter, 2011)
When people think of bioregionalism they often envision of watersheds, biotic zones, fauna and flora types, weather patterns, decentralization, and autonomy. Intriguingly, in his seminal essay “Living by Life: Some Bioregional Theory and Practice,” bioregionalist Jim Dodge (1981) cites “spirit places” as the third tenet of bioregionalism. However, aside from mentioning Mt. Shasta and the Pacific Ocean as “psyche-tuning power-places,” he offers little in the way of how spirits places shed light on bioregionalism. This paper, drawing on two research trips among the highlanders of Northeast Cambodia, concludes that a bioregional theory that does not include spirit places is myopic. Taken in the highlander context in Cambodia, such a theory is utterly meaningless. The Brao, Tampuan, Bunong and other ethnic minorities of Ratanakiri province show us that bioregionalism is more than geographical separation points and intimate knowledge of local ecology; knowing where spirits dwell and how to deal with them is an equally and quite possibly more important aspect of living sustainably and fruitfully in one’s bioregion. Numerous environmental writers have put forth that indigenous people worldwide are our best teachers for living symbiotically with nature, yet most of these authors are selective students; they are interested in biology lessons, but not spiritual ones. But biology and spirituality are not separate entities for the highlanders of Northeast Cambodia; they are one in the same. This paper argues the point that bioregionalism must take in account spiritual dimensions of the landscape as pointed out by indigenous people.